Narcissistic Personality Disorder (NPD) Perspektif Al-Qur'an (Analisis Tafsir Al-Manar QS: Luqman:18) - Mohamad Mualim; Muhammad Ghifari; Shabira Ayu Juliandini (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
Narcissistic Personality Disorder (NPD) is a personality disorder characterized by a sense of superiority, a need for praise, and a lack of empathy for others. In modern psychology, NPD is often associated with stressful childhood parenting or excessive praise, and has a negative impact on social relationships and psychological well-being. In Islam, arrogant behavior and feeling superior to others have received serious attention, as emphasized in the Qur'an, especially QS. Luqman: 18. The verse explicitly warns humanity to stay away from arrogance and pride, which are substantially similar to the characteristics of NPD. This article aims to analyze Narcissistic Personality Disorder (NPD) from the perspective of the Qur'an by examining the Tafsir Al-Manar on QS. Luqman: 18. Using a descriptive qualitative method based on the study of interpretation, this study identifies the relevance of the verse to the phenomenon of NPD in the context of modern psychology. Tafsir Al-Manar written by Muhammad Abduh and Rasyid Rida emphasizes that arrogance not only has an impact on individuals psychologically but also has the potential to damage social order and interpersonal relationships. The findings of this study indicate that Islamic teachings, through QS. Luqman: 18 and its explanation in Tafsir Al-Manar, offer practical and spiritual solutions to deal with narcissistic tendencies. Islam encourages an attitude of tawadhu' (humbleness), self-introspection, and strengthening spirituality through the practice of dhikr, contemplation, and controlling lust. Previous studies have also shown that an approach based on Islamic values ​​can help reduce the need for external validation and improve an individual's psychological well-being. Thus, this study emphasizes the importance of integrating modern psychological understanding with Islamic teachings for a more holistic treatment of narcissistic personality disorder. In addition, the results of this study provide broad social and religious implications, namely the creation of a more harmonious society, a decrease in authoritarian and exploitative behavior in leadership, and strengthening interpersonal relationships based on empathy and sincerity. Therefore, the implementation of the values ​​of the Qur'an and the practice of Islamic teachings in everyday life can be an effective instrument to prevent and handle narcissistic behavior sustainably.